Kapandji pinning and tuberosities fixation of three- and four-part fractures of the proximal humerus - Bonnevialle, Nicolas (Springer Berlin Heidelberg, 2013)
PURPOSE: The Kapandji pinning was initially described for the treatment of surgical neck fractures of the humerus in young patients. The aim of our study was to evaluate functional and radiological outcomes of the Kapandji modified technique in displaced complex three- and four-part fractures. METHODS: From 2005 to 2009, 32 patients (23 three-part and nine four-part fractures) were included retrospectively. The mean age was 63 years old (range, 22–86), and the dominant shoulder was involved in 40 % of the cases. RESULTS: At a mean follow up of 25 months (12–72), the mean absolute Constant score achieved 68 points (35–98) and adjusted score 80 % (47–100). Patients had an average forward elevation of the shoulder of 132° (80°–180°), an average external rotation of 36° (0°–90°), and an average internal rotation to the level of L1 (sacrum to the level of T6). The older the patients were the worst was the active anterior elevation recovery (r = −0.3; p = 0.01). Reduction and fixation of initial varus-displaced fractures was not as reliable as in valgus. In eight cases (25 %), K-wire migrations were observed and were correlated with age over 70 years old (p = 0.001). Two partial osteolysis of the greater tuberosity and two avascular necrosis of the humeral head (one was associated with a non-union) were identified. Moreover, three patients developed adhesive capsulitis. CONCLUSION: The Kapandji technique with fixation of tuberosities provides satisfactory results for the treatment of complex proximal fractures of the humerus. However, we do not recommend this technique for patients older than 70 years and in cases of varus displaced fractures.